I want to keep on exercising but I don't: The negative impact of momentary lacks of self-control on exercise adherence. (September 2016) - Englert, Chris; Rummel, Jan
Abstract: Objectives: We investigated the impact of state and trait self-control strength on exercise execution. We hypothesized that state self-control strength is reduced on days that are perceived as stressful and that reductions in self-control strength result in a lower likelihood to work out. Additionally, trait self-control strength may affect the execution of workout plans. Design: University students, who stated that they have not been exercising regularly for at least one month, filled in a trait self-control inventory, a personality questionnaire, and were instructed to perform a daily workout over a one-week period. Perceived stress levels, state self-control strength, and workout completion were assessed on a daily basis. Results: Results revealed that people were less likely to exercise on days they perceived as stressful. State self-control mediated the relation between stress and exercise completion. Trait self-control and other personality variables did not affect workout completion. Conclusions: Results indicate that daily stress is associated with self-control depletion and a lower likelihood to work out. Highlights: People are less likely to exercise on days they perceive as stressful. Daily stress is associated with lower levels of self-control strength. State self-control mediates the relation between stress and exercise completion.